IT Governance and Its Role in Enhancing Yemeni Universities’ Responsiveness to Contemporary Digital Transformations - Mansour Saleh AL-ABDI; Mabrouk Saleh Al-SOUDI (Social Empowerment Journal, 2024)
The study aimed to highlight the role of Information Technology governance in enhancing the response of Yemeni universities to contemporary digital transformations. It employed a descriptive analytical methodology, utilizing content analysis of official documents and websites of Yemeni universities, in addition to qualitative interviews with a sample of individuals responsible for information technology centers in 23 public and private universities The qualitative analysis of the data revealed that Yemeni universities face several challenges that impact their ability to adapt to rapid technological changes in higher education. Notably, private universities exhibited greater flexibility compared to their public counterparts. The study underscores the urgent need to adopt effective governance strategies, increase awareness of the importance of Information Technology governance, and allocate necessary financial and technical resources. Furthermore, the findings indicate that enhancing the responsiveness of universities to digital transformations requires collaboration among all stakeholders, including government entities and the private sector. The study also emphasizes the necessity of establishing a national center for Information Technology governance in higher education, developing comprehensive strategies that align with global developments, and creating training programs to enhance the competencies of human resources in this field. In light of these results, the study offers practical suggestions and recommendations that can guide efforts to strengthen the capacity of Yemeni universities to respond to digital transformations through Information Technology governance, ultimately improving the quality of higher education in Yemen.